A new subspecies of Dysiatus from the Sangihe and Talaud islands (Coleoptera: Cerambycidae, Prioninae) - Missori, Paolo; Ercoli, Lucia (Zootaxa, 2019)
The prioninae genus Dysiatus consists of one large species, Dysiatus melas (Pascoe, 1869), occurring on Sulawesi Island, Indonesia. Like other Asian prioninae, its habitat is limited to mountain rainforests, but its distribution does not appear to be threatened because of the large area of suitable habitat available. The new subspecies described here was collected in the remote Sangihe Islands within the province of North Sulawesi. Other specimens of this subspecies have been reported from the Talaud Islands, which lie northeast of the Sangihe Islands.